STEAM Education for Transformative Mathematics Learning - Lamichhane, Basanta Raj (Saptagandaki Journal, 2021)
In this paper, I have tried to explore hegemonic western cultural worldview which heavily influences the traditional disciplinary egocentric curriculum practices. Western hegemonic culture's overriding inspirations in mathematics education have established western modern worldviews, culture, and traditions as universal standards. Through the so-called standard norms and values, the powerful countries (mainly western and European countries) have seized others' cultures, values, and perspectives and thus developed the culture of silence. Conventional disciplinary egocentrism indoctrinates hegemonic culture that makes the learners unaware of their ways of being, knowing, and doing. It severely affects less powerful (politically, economically and technologically) countries' education systems by pervading instrumental, decontextualized and bureaucratic thought and beliefs. It engulfs humanitarian, biocultural, political, and spiritual perspectives of mathematics education. It signifies that we urgently need to revitalize mathematics education by incorporating newly emerging perspectives; one such perspective might be STEAM education. I would like to discuss the different perspectives of STEAM education and explore how STEAM education contributes to creating new synergetic learning spaces in mathematics education by enhancing transformative learning practices. The primary concern of STEAM education is to acknowledge local and contextual ways of beings, knowing, and doing. The recognition of the local cosmological knowledge, perspectives, and values support authenticate the learning process. The learning authentication widens the possibilities of active engagement of learners in the learning and decision-making process by deploying creative, critical, and imaginative thinking and skills. A deep engagement in a multi/inter/transdisciplinary learning process embraces the learners into bio-cultural differences; the lifelines of the human being support developing awareness, self-consciousness, and spiritual sensibility. STEAM perspectives always focus on enriching transformative agendas to create more authentic, inclusive, and empowering educational practices. It also empowers the learners to act as change agents for enhancing socially, ecologically, and bio-culturally just society that underpins to transform mathematics education.